2015
DOI: 10.1111/ppa.12314
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and early evolution of fungicide resistance in North American populations of Zymoseptoria tritici

Abstract: Although fungicide resistance in crop pathogens is a global threat to food production, surprisingly little is known about the evolutionary processes associated with the emergence and spread of fungicide resistance. Early stages in the evolution of fungicide resistance were evaluated using the wheat pathogen Zymoseptoria tritici, taking advantage of an isolate collection spanning 20 years in Oregon, USA, and including two sites with differing intensity of fungicide use. Sequences of the mitochondrial cytb prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 39 publications
2
64
0
3
Order By: Relevance
“…STB pathogen isolates with resistance to QOIs developed quickly, following a few years of intensive use, and existed before these fungicides were deployed. Once deployed, the resistant isolates dramatically increased in frequency in Europe, Tunisia, Morocco, and the United States (25). STB fungal insensitivity to DMIs has gradually been observed during the past 10-15 years, and the first isolates have already been reported in recently introduced SDHIs from regions with high disease pressure and intensive use of fungicides (87).…”
Section: Evolution Of Resistance To Fungicides In Pathogen Populationsmentioning
confidence: 98%
“…STB pathogen isolates with resistance to QOIs developed quickly, following a few years of intensive use, and existed before these fungicides were deployed. Once deployed, the resistant isolates dramatically increased in frequency in Europe, Tunisia, Morocco, and the United States (25). STB fungal insensitivity to DMIs has gradually been observed during the past 10-15 years, and the first isolates have already been reported in recently introduced SDHIs from regions with high disease pressure and intensive use of fungicides (87).…”
Section: Evolution Of Resistance To Fungicides In Pathogen Populationsmentioning
confidence: 98%
“…The G143A substitution was present in 24 different haplotypes, with phylogenetic analysis indicating four independent de novo origins. Estep et al (2015) subsequently investigated cytochrome b haplotypes in Z. tritici populations from North America, finding G143A present in several haplotypic backgrounds, with phylogenetic analysis supporting multiple parallel origins. However, they also report evidence of reduced mitochondrial genetic diversity among isolates with G143A, so the overall picture is of a selective sweep intermediate between a soft and hard sweep, following a small number of parallel de novo mutations.…”
Section: (3) Fungicidesmentioning
confidence: 99%
“…Collections were made by Estep et al. () in 2012 from two fungicide trials, one located within a commercial winter wheat field in the Northern Willamette Valley (North Valley), and the other at the Hyslop Field Laboratory in the Southern Willamette Valley (South Valley). Isolates were screened for the presence of the G143A mutation by Estep et al.…”
Section: Methodsmentioning
confidence: 99%
“…Isolates were screened for the presence of the G143A mutation by Estep et al. () using polymerase chain reaction‐restriction fragment length polymorphism (PCR‐RFLP). Isolates used in this study were phenotypically confirmed on azoxystrobin amended, and unamended Petri plates following exact procedures detailed in Hagerty and Mundt ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation